ECONOMIC, SOCIAL AND POLITICAL IMPEDIMENTS OF NIGERIAN OIL AND GAS INDUSTRY - Ichima, Egor (Revista Inclusiones, 2020)
Nigeria is one of the largest producers of petroleum and gas which are significant resource base of the Nigerian economy contributing approximately 80 percent of government revenue and accounting for more than 90 percent of the country’s foreign exchange earnings. The survey was carried out to find out economic, social and political impediments of Nigerian oil and gas industry on the base of questioning over 500 persons of different managerial level from 11 companies. The findings ascertained the significant positive effects of oil and gas sector prices on competitiveness in the oil and gas sector and highlights the positive and significant effects of theft and vandalism on the overall growth of the Nigerian oil and gas sector. This study has provided evidence ascertaining the linkages between contemporary issues and challenges inherent in the Nigerian oil and gas industry and its prospects for competitiveness, operational effectiveness and overall growth.